Rediscovery and redescription of Coenagrion persicum (Lohmann 1993) with description of the female, and some notes on habitat selection (Odonata: Coenagrionidae) - Schneider, Thomas; Ikemeyer, Dietmar; Ferreira, Sónia; Müller, Ole (Zootaxa, 2016)
Coenagrion persicum was described by Heinrich Lohmann in 1993 on the basis of a single male and two larvae captured in 1937 by E.W. Kaiser in Lorestãn Province (W-Iran). In June 2015 two of the authors (TS and DI) rediscovered individual-rich populations of this species in two Iranian provinces (Lorestãn and Esfahãn). We could confirm the structural differences of the male appendages between C. persicum and C. pulchellum based on a larger number of specimens than in the original description. The structural differences from C. pulchellum in females and their phenotypic variation pattern is described. Coenagrion persicum and C. pulchellum are also genetically distinct regarding two nDNA gene fragments: arginine methyltransferase (PRMT) and phosphoglucose isomerase (PGI). In contrast with C. pulchellum, C. persicum prefers small springs and running waters with rich herbal vegetation. Our faunistic data indicate that the species is present in the mountains between 1800 m and 2300 m a.s.l.. The species seems to be restricted to W-Iran, where it co-occurs with other rheophilic species.